The mode of gas accretion onto star-forming galaxies - Marinacci, F; Binney, J; Fraternali, F; Nipoti, C; Ciotti, L; Londrillo, P (2010)
It is argued that galaxies like ours sustain their star formation by transferring gas from an extensive corona to the star-forming disc. The transfer is effected by the galactic fountain -- cool clouds that are shot up from the plane to kiloparsec heights above the plane. The Kelvin-Helmholtz instability strips gas from these clouds. If the pressure and the the metallicity of the corona are high enough, the stripped gas causes a similar mass of coronal gas to condense in the cloud's wake. Hydrodynamical simulations of cloud-corona interaction are presented. These confirm the existence of a critical ablation rate above which the corona is condensed, and imply that for the likely parameters of the Galactic corona this rate lies near the actual ablation rate of clouds. In external galaxies trails of HI behind individual clouds will not be detectable, although the integrated emission from all such trails should be significant. Parts of the trails of the clouds that make up the Galaxy's fountain should be observable and may account for features in targeted 21-cm observations of individual high-velocity clouds and surveys of Galactic HI emission. Taken in conjunction with the known decline in the availability of cold infall with increasing cosmic time and halo mass, the proposed mechanism offers a promising explanation of the division of galaxies between the blue cloud to the red sequence in the colour-luminosity plane.